2019
DOI: 10.1111/poms.13063
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Information Technology and Communication on Medical Malpractice Lawsuits

Abstract: Health care organizations have substantially invested in Health Information Technology (HIT) as part of an effort to improve quality. However, many hospitals fail to generate positive returns on this significant investment, based on reimbursements for quality measures through the Affordable Care Act (ACA). Given the high cost of lawsuits, we investigate if HIT adoption reduces lawsuits, and their attendant costs, as another consideration in HIT payoffs. We use operational transparency theory to develop hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…We found seven performance indicators [17] [21] [27] [33] [40] [50] that do not fit within the four previously mentioned dimensions. For example, number of lawsuits, [17] malpractice insurance premium [21], and reuse of data [33]. We bundled these performance indicators into the category "other".…”
Section: Othermentioning
confidence: 95%
See 1 more Smart Citation
“…We found seven performance indicators [17] [21] [27] [33] [40] [50] that do not fit within the four previously mentioned dimensions. For example, number of lawsuits, [17] malpractice insurance premium [21], and reuse of data [33]. We bundled these performance indicators into the category "other".…”
Section: Othermentioning
confidence: 95%
“…Patient engagement HIT describes functionalities such as patient monitoring or telehealth [16]. Administrative HIT describes functionalities such as ERP systems that integrate and manage various administrative and financial processes within hospitals [1] [3] [17]. For an overview of types of HIT functionalities in hospitals, see Figure 2.…”
Section: Hit Functionalities and Their Measurementmentioning
confidence: 99%
“…For example, Sharma et al. (2019) showed that the use of HIT systems reduced the number of legal lawsuits against providers. In particular, hospitals with higher adoption levels were more effective at reducing lawsuits.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Finally, compliance with mandated HIT systems such as PDMP also offers providers protection against liability claims. For example, Sharma et al (2019) showed that the use of HIT systems reduced the number of legal lawsuits against providers. In particular, hospitals with higher adoption levels were more effective at reducing lawsuits.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation